A avaliação da aprendizagem pela ótica da taxionomia de Bloom: quais são as dimensões privilegiadas pelos professores de administração? - Silva, Josué José da (2015)
The Brazilian private Higher Education had been receiving various government incentives. This fact favored this sector and resulted in a consistent consolidation movement. At the same time, the Government had been more effective to monitor Higher Education Institutions by creating new performance standards and evaluating its results. In this scenario, assessment methods used by professors were in focus, so it naturally refers to their assessment processes. On the other hand, professors prepare students to standardized assessments that evaluated their home institutions and which are formulated by INEP (Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira), the institute that evaluate the level of the Brazilian Higher Education institutions. Thus, the objective of this study is to verify whether the Higher Education professors from Brazilian Management courses use, and if they do, with which frequency, the Cognitive Domain from the Taxonomy of Educational Objectives in their assessment instruments in order to measure whether these very objectives were reached by the teaching/learning process. The theoretical framework of this study was based on Bloom et al (1972) and other authors who contributed to the elaboration of the research instrument which allowed us collecting useful data to analyze (i) the profile of the professors; (ii) the assessment tools and (iii) the adherence of these instruments to the Taxonomy. The used methodology, that is, the exploratory search, allowed the introduction of a specific instrument to collect primary data directly from professors. Moreover, the Statistical analysis confirmed a strong relation between the constructs, corroborating the findings from the theory of Bloom et al (1972), which show that the categories are inseparable from each other. We conclude that professors use the categories expected by the Taxonomie in a greater or lesser extent according to the IES (Higher Education Institution) for which they work; to which type of regime they work under; and to the concentration area in which they teach classes. This variation, nonetheless, does not show a significant preference for the use of a category over the use of another.